Management and Outcomes of Patients With Radiotherapy Interruption During the COVID-19 Pandemic - Ying, Xiaofang; Bi, Jianping; Ding, Yi; Wei, Xueyan; Wei, Wei; Xin, Fang; Xiao, Chuangying; Hu, Desheng; Verma, Vivek; Han, Guang (Frontiers in Oncology, 2021)
Purpose: This retrospective observational study examined patients who experienced radiotherapy (RT) interruption during the Wuhan lockdown for the novel coronavirus disease 2019 (COVID-19) pandemic. Materials and methods: The data of all patients whose RT was interrupted during the Wuhan lockdown from January 23 to April 8, 2020 were collected. Patient-, cancer-, and treatment-related characteristics were analyzed, along with interruption time, disease progression type, and survival status. The methods employed in order to compensate for RT interruption were also described. Results: There were altogether 129 cancer patients whose RT was interrupted. Nineteen (14.7%) patients experienced a total interruption time of at most 7 days; the interruption time was 8-14 days for 27 (20.9%) patients, and 15 or more days for 47 (36.4%) patients. The remaining 36 (27.9%) patients did not come back to our hospital for further RT. We first describe our experience with re-immobilization and/or re-planning (n=17) as well as dose compensation/adjustment. Of the 40 definitive radiotherapy patients, 37 had squamous cell carcinoma of nasopharyngeal, lung, or cervical origin. Most patients (85/93, 91.4%) were followed up for more than one year. Among the 40 patients who received definitive radiotherapy, 9 patients experienced disease progression and 5 patients died. Three of the 7 (42.9%) patients who did not finish radiotherapy after interruption died, as compared to only 2 of the 33 (6.1%) patients who completed radiotherapy. EQD2 (equivalent dose in 2Gy fractions) at the time point of RT interruption was calculated. Five of the six patients (83.3%) who received EQD2 ≤10Gy suffered from disease progression, compared with 4 of the 34 (11.8%) patients who received EQD2 >10Gy. For the 7 definitive radiotherapy cases who did not finish radiotherapy, 3 received systemic anti-cancer treatments and 3 died (all of whom did not receive further systemic therapies). Conclusions: This study provides the longest follow-up for the outcomes of RT interruption during COVID-19 pandemic to date. It cannot imply causation but implies that completing RT is important, along with the utility of having patients remain on systemic therapies if RT is to be interrupted.